A cognitive load delays predictive eye movements similarly during L1 and L2 comprehension. Issue 2 (6th March 2017) - ITO, AINE; CORLEY, MARTIN; PICKERING, MARTIN J.
Abstract : We used the visual world eye-tracking paradigm to investigate the effects of cognitive load on predictive eye movements in L1 (Experiment 1) and L2 (Experiment 2) speakers. Participants listened to sentences whose verb was predictive or non-predictive towards one of four objects they were viewing. They then clicked on a mentioned object. Half the participants additionally performed a working memory task of remembering words. Both L1 and L2 speakers looked more at the target object predictively in predictable- than in non-predictable sentences when they performed the listen-and-click task only. However, this predictability effect was delayed in those who performed the concurrent memory task. This pattern of results was similar in L1 and L2 speakers. L1 and L2 speakers make predictions, but cognitive resources are required for making predictive eye movements. The findings are compatible with the claim that L2 speakers use the same mechanisms as L1 speakers to make predictions.